DETERMINAN CASH HOLDING PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Tanujaya, Cindy; Susanto, Liana (Jurnal Paradigma Akuntansi, 2023)
This study aims to acquire empirical evidence to determine whether leverage has a negative impact on cash holding, whether profitability has a positive impact on cash holding, whether tangible asset has a negative impact on cash holding, whether firm size has a positive impact on cash holding and whether investment opportunities have a positive impact on cash holding for manufacturing companies in Indonesia. This research uses purposive sampling method to collected data and Eviews 12 to processed its data. This research uses sample of 58 manufacturing companies listed on Indonesian Stock Exchange for the period 2017-2020. The results of this research are firm size and investment opportunities have no impact on cash holding, leverage and tangible assethave a significant negative impact on cash holding, and profitability has a significant positive impact on cash holding.